Linking Protective Strategies Effects to Manage the COVID-19 Risk on Global Environment: Fresh Evidence from the Best Responsive Approach - Abbasi, Kashif Raza; Hussain, Khadim; Noureen, Rani Saima; Bashir, Uzma (International Journal of Energy Economics and Policy, 2021)
The coronavirus pandemic appeared as the most critical global health disaster of this century to date, which caused environmental, health, and energy crises worldwide. Humanity has encountered the most challenging health emergency since the earlier calamity of World War-II, which posed economic crisis, social, and environmental challenges to entire communities. It severely disrupted the global economy, international relations, and social interactions. Global efforts initiated to mitigate the COVID-19's rapid spread by launching testing facilities, quarantining suspected cases, treating affected patients, restricting large social gatherings, and imposing full or smart lockdown measures. This research evaluated the strengths and weaknesses of twenty selected countries' best responsive model in overcoming the global crisis and environmental effects and 20 chosen countries responsive strategies. Findings suggest eight crucial strategies/core recommendations to minimize environmental effects, air quality and rivers water quality, reflected better for the short-term, and biodiversity thrived after the COVID-19 outbreak. The study suggests self-produced medical equipment and consolidated supply chain operations to avoid relying on other countries. This article suggests empowering companies to practice social responsibility policies to provide resources for producing environmentally friendly products. Keywords: COVID-19; Novel Coronavirus; learning lessons; overcome crisis; environmental effect JEL Classifications: H51, H52, H53 DOI: https://doi.org/10.32479/ijeep.11393